2017
DOI: 10.3758/s13414-017-1360-3
|View full text |Cite
|
Sign up to set email alerts
|

Duration compression induced by visual and phonological repetition of Chinese characters

Abstract: Our prior experience heavily influences our subjective time. One of such phenomena is repetition compression, that is, repeated stimuli are perceived shorter than novel stimuli. However, most of the studies on repetition compression used identical stimuli, leaving the question whether similar repetition effects could take place in phonological and semantic level repetition. We used Chinese characters to manipulate different levels of repetition in a duration discrimination task. We replicated earlier findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…This is important because the extant line of investigation has mainly focused on the effects of whole-stimulus repetition (e.g., picture, simple symbol, and character). It is important to highlight that these studies demonstrated the repetition duration compression (Matthews and Gheorghiu, 2016) and explained the phenomenon with bases on the predictive coding account (Schindel et al, 2011;Pariyadath and Eagleman, 2012;Jia and Shi, 2017;Saurels et al, 2019). Under this account, the magnitudes of the repetition effect reflect the discrepancy between the predicted and actual items in terms of their physical characteristics.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…This is important because the extant line of investigation has mainly focused on the effects of whole-stimulus repetition (e.g., picture, simple symbol, and character). It is important to highlight that these studies demonstrated the repetition duration compression (Matthews and Gheorghiu, 2016) and explained the phenomenon with bases on the predictive coding account (Schindel et al, 2011;Pariyadath and Eagleman, 2012;Jia and Shi, 2017;Saurels et al, 2019). Under this account, the magnitudes of the repetition effect reflect the discrepancy between the predicted and actual items in terms of their physical characteristics.…”
Section: Introductionmentioning
confidence: 84%
“…In other words, neural responses are suppressed for the predicted signals (repeated stimuli) and activated or even enhanced for the surprising stimuli (oddball/novel stimuli). The view of predictive coding was supported by a large number of studies (Matthews, 2011;Schindel et al, 2011;Pariyadath and Eagleman, 2012;Birngruber et al, 2015;Jia and Shi, 2017;Saurels et al, 2019). In this framework, the size of the repetition effect should be dependent on the similarity between the predicted and actual signals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations